What Mentors Tell Us About Acknowledging Effort and Sustaining Academic Research Mentoring: A Qualitative Study. Issue 1 (2019) - Mancuso, Carol A.; Berman, Jessica R.; Robbins, Laura; Paget, Stephen A.
Abstract : Introduction: Continuing education is necessary to foster new and effective research mentoring skills. We asked faculty about their research mentoring practices and what would support their skills and abilities as ongoing and effective research mentors. Methods: Twenty-two experienced mentors were interviewed and asked about perceived areas for improvement, and challenges and facilitators to continued research mentoring. Responses were analyzed with qualitative techniques using semistructured interviews, grounded theory, and a constant comparative analytic strategy. Results: The average time since the completion of the doctoral degree was 26 years. Twenty-one participants believed that more comprehensive institutional acknowledgment for their efforts would enhance research mentoring. This specifically included acknowledging their time spent and service (ie, effort) in multiple in-person and behind-the-scenes tasks. These research mentoring efforts were largely viewed as overlooked by the traditional focus on the achievement of tangible outcomes. Participants thought that a formal plan to organize research mentoring (such as a mentor's charter, and continuing education tailored to both novice and experienced research mentors) was needed to promote evolution of skills and documentation of time and service. Possible methods to support research mentors were suggested and included financial support for travel to national meetings, assistance in developing new projects, and consideration of mentoring activities in the process for academic promotion. Discussion: Research mentors wanted their achievements, time spent, and service (ie, effort) to be acknowledged by the institution. A formal written mentoring charter and corresponding continuing education could facilitate acknowledging achievements, time, and service and thus help to sustain academic research mentoring.